2018
DOI: 10.1136/bmjopen-2018-023624
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic malaria parasitaemia and seizure control in children with nodding syndrome; a cross-sectional study

Abstract: ObjectivePlasmodium falciparum is epileptogenic and in malaria endemic areas, is a leading cause of acute seizures. In these areas, asymptomatic infections are common but considered benign and so, are not treated. The effects of such infections on seizures in patients with epilepsy is unknown. This study examined the relationship between P. falciparum infection and seizure control in children with a unique epilepsy type, the nodding syndrome.DesignThis cross-sectional study was nested in an ongoing trial ‘Doxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Similar conclusions were drawn from community studies in Cameroon 45,46 . More recent reports have highlighted the correlation of malaria with disease expression and outcome in children with nodding syndrome 2,47 . This led to promotion of intervention with doxycycline to eradicate or prevent malaria in children with nodding syndrome 47,48 .…”
Section: Resultssupporting
confidence: 63%
“…Similar conclusions were drawn from community studies in Cameroon 45,46 . More recent reports have highlighted the correlation of malaria with disease expression and outcome in children with nodding syndrome 2,47 . This led to promotion of intervention with doxycycline to eradicate or prevent malaria in children with nodding syndrome 47,48 .…”
Section: Resultssupporting
confidence: 63%
“…Having said that, a kaleidoscope of studies over the years revealed various potential causes, features and/or associations of NS with infections, environmental factors, psychological/psychiatric factors, neurodegeneration, and autoimmunity affecting the central nervous system (CNS) [ 1 , 5 , 9 , 11 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the present analysis, 150 samples were available of 154 recruited in the parent study. This area is located in northern Uganda bordering South Sudan and is inhabited by the Acholi people [ 22 ]. The primary economic activity is subsistence farming complemented with small-scale animal husbandry.…”
Section: Methodsmentioning
confidence: 99%